Optimización del sistema de gestión de inventarios de la empresa ASTAP aplicando la homología persistente - Abalco Días, Addis Scarlett (2018)
The present wok focuses on the optimization of the inventory management system of the company ASTAP, through the application of topological data analysis ATD, in order to identify the significant variables of the inventory data cloud, for, in base a, perform an ABC segmentation of the products and propose an adequate model of inventory.